Physical, mechanical and thermal conductivity of concrete containing granulated recycled pet bottle - Misri, Zainora (2020)
Concrete is the most extensively used material in the construction industry. Its high demand has threatened the environment and led to the depletion of natural resources such as sand, which is the basic material of concrete. Many strategies have been proposed to overcome these issues, such as reusing waste materials in concrete production. Therefore; the aim of this study is to investigate the effect of granulated recycled polyethylene terephthalate (PET) bottle as sand replacement on physical, mechanical and thermal conductivity of concrete. In this research, the ground PET were sieved passing 5 mm sieve size with 5%, 10% and 15% replacement amount. The total of 120 samples with cube, cylinder, beam and panel size were cast. At fresh stage, slump test was conducted to determine the workability of concrete. As of hardened stage, density, water absorption, compressive strength, split tensile strength, flexural strength, modulus of elasticity and thermal conductivity were tested on samples at 7 and 28 days. The percentage of PET replacement that up to 10% had obtained the target strength of 30 MPa concrete grade, and acceptable value of thermal conductivity which performs same properties of normal concrete. However, the recommended percentage of PET aggregate was up to 5% due to its achievement as highest compressive strength, split tensile strength, flexural strength and modulus of elasticity which the values are 33.9 MPa, 3.20 MPa, 4.3 MPa and 21111 MPa, respectively. Based on the overall physical, mechanical and thermal performance, concrete with 5% PET replacement is appropriate to be used in concrete production. Therefore, PET can be used as an alternative material of the aggregate in producing concrete in a construction industry.